PENINGKATAN KREATIVITAS DAN PRESTASI BELAJAR AKUNTANSI PADA MATERI PENJURNALAN DI KELAS XB SMK PL TARCISIUS 2 SEMARANG TAHUN PELAJARAN 2011/2012 MELALUI MEDIA PAKU - Andriawati, Yohana Richa (Dinamika Pendidikan, 2012)
The objective of this research is to improve accounting studentsâ creativity and achievement in the lesson of journalizing on XB class in SMK PL Tarcisius 2 Semarang in the Academic Year of 2011/2012 by PAKU media. It was a class action research which designed in two cycles. The subjects of the study were students of class XB in SMK Tarcisius 2 Semarang in the academic year of 2011/2012. The objects of this research were accounting learning creativity and accounting academic achievement. The data were collected by documentation, observation and tests. The results showed that (1) accounting learning creativity in learning journalizingÂ  by PAKU media increased up to 12% from the initial condition to the first cycle, and rose 11% from the first cycle to the second cycle and 23% from the initial condition to the second cycle. (2) studentsâ accounting academic achievement in learning journalizingÂ  by PAKU media also increased up to 25% from the initial condition to the first cycle, rose 17%Â  from the first cycle to the second cycle, and 42% from the initial condition to the second cycle.